(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
This paper examines points of convergences between Karl Marx and Amartya Sen's conception of freedom. It begins by providing a brief interpretation of Karl Marx's ideas on freedom, and brings in some of these interpretations as complementary perspectives to Sen's conception of freedom. While it can be said that Marx did not intentionally develop systematic ideas on freedom and rights, it is however arguable that Marx himself had a very strong position on these issues, and that his ideas and perspectives may be used to further enlighten critical reflections on Sen's suggestions. One goal of this undertaking is to raise some theoretical ideas in the conceptualisation of solidarity specifically couched in Marx and Sen's language of freedom and rights.